High temperature biaxial compressive strength of a commercial isotropic ultrafine grain graphite. Issue 1 (February 2021) - Centofante, L; Monetti, A; Meneghetti, G
Abstract: Graphite is widely used in industrial applications, thanks to its excellent high temperature resistance. Therefore, its mechanical strength under combined stress at high temperature is an important issue for structural design. This work reports biaxial compressive data of an isotropic ultrafine grain graphite, the POCO EDM-3. Uniaxial tests have been first performed at room temperature with plane specimens, in order to obtain the stress strain curve for this material. Compressive tests have been then carried out with different notched geometries, both at room temperature and at 1000°C, in order to evaluate the biaxial compressive strength. Since plastic deformation was observed in uniaxial compressive tests with plane samples, elastic-plastic simulations have been performed with the FE code Ansys®, in order to assess the stress state at failure. The applicability of the Von Mises yield criterion has been evaluated, by comparing the equivalent Von Mises stresses at failure in different notched geometries. The tests demonstrated that, at room temperature, this type of graphite plastically deform in compression and that the Von Mises criterion can be used in order to evaluate the stress state. Moreover, the comparison between the failure loads at room temperature and at 1000°C showed that the resistance increases as the temperature increases.